Library managers' disposition to work politics in Oyo state (2017)
The library is an important organ of human resources management where people with formally assigned roles work together to achieve the parent institutional goals. The direct handling of the people served as an integral part of the library managers' line of authority and vice-versa. The library managers are handled by the chief executive of their respective institutions. The direct work relationship between the library managers and the chief executives of their respective institutions as it is in all organization requires a bit of office politics. The general trends of the play of office politics by the heads of libraries were investigated. The findings depicts that majority of the library managers were not politically inclined in their administrative style with their respective institutions' chief executives. The need to develop the good political will and socialise with their respective institutions' chief executives to win uncommon approval was recommended amongst others.